Diversity of vaginal microbiota associated with bacterial vaginosis and the impact on pregnancy outcomes in HIV-infected and uninfected women. - Mugabe, Muchaneta (Department of Pathology, 2019)
The composition of vaginal microbiota in pregnancy is important as it may influence susceptibility to adverse pregnancy outcomes. Dysbiosis of the vaginal microbiota caused by the replacement of protective resident microorganisms such as Lactobacillus spp. by anaerobic bacteria is known as bacterial vaginosis (BV). BV is prevalent in women of African descent and may be a cause of higher rates of adverse birth outcomes in these women. Adverse birth outcomes have been reported to be higher in HIV-infected women both on treatment or treatment naïve compared to HIV-uninfected women. The relationship between the vaginal microbiome, HIV and pregnancy outcomes has not yet been established in Zimbabwean women, nor reported in sub Saharan Africa, where the burden of disease is high. Identification of specific organisms and immune factors associated with adverse pregnancy outcomes could lead to interventions or diagnostic algorithms to prevent and predict these outcomes in this population. We recruited 420 pregnant Zimbabwean women [48 (11.4%) HIV infected, 372 (88.6%) HIV uninfected], between 13-35 weeks of gestation with a median gestational age of 30 weeks. Vaginal swabs were collected at enrolment and women were followed until pregnancy outcome was determined. Bacterial DNA was extracted from the vaginal swabs using an optimized Phenol chloroform extraction method with an addition of an enzymatic cocktail step. Library preparation was done using the Universal primers (515F/806R) for the hypervariable V4 region of the 16S rRNA gene. For the first PCR KAPA Hotstart + primers (Roche Lifescience, UK), were used for amplification. After amplification AMPure XP beads (Beckman Coulter, Brea, CA, USA) were used for cleaning of the PCR products at all stages. For the second PCR Nextera XT, Index Kit (Illumina) was used adding unique sequencing adapters to the amplicons. Quantitative PCR was used for library quantification and pooled libraries were the sequenced using Illumina MiSeq. Upstream analysis of sequencing data was done using QIIME and UPARSE and downstream analysis using custom R scripts on samples with good quality reads (>5000). Concentrations of 27 cytokines were measured in vaginal swab samples using a Bio-Plex Pro Human Cytokine 27- plex Assay (Bio-Rad Laboratories Inc., USA). Assay plates were read using a Bio-Plex Suspension Array Reader (Bio-Rad Laboratories Inc., USA). Data were analyzed using Bio-Plex manager software (version 4). Cytokine levels that were below the lower limit of detection of the assay were reported as the mid-point between zero and the lowest detectable level measured for that given cytokine. Pregnant women in this cohort had vaginal microbiota that clustered into 3 main community state types (CST): 109/356 (31%) CST1 - Lactobacillus iners dominant, 102/356 (29%) CST2 - Lactobacillus crispatus dominant and 145/356 (41%) CST3 - Gardnerella vaginalis dominant. There was a high prevalence of dysbiotic vaginal communities and L. iners was the predominant taxa found in > 90% of the women. When exploring whether the vaginal microbiota is associated with pregnancy outcomes, L. iners was highly associated low birth weight (LBW) and small for gestational age deliveries (SGA) while in contrast G. vaginalis was associated with normal birth outcome. There were no strong relationships identified between preterm birth (PTB) and vaginal microbiota. There was a strong correlation between vaginal microbiota and proinflammatory and adaptive cytokines. BV associated organisms (Gardnerella, Aerococcus, Prevotella Coriobacteriaceae and Dialister) were highly inflammatory while Lactobacillus spp were associated with low inflammation. Low levels of IL-13 and PDGF-BB cytokines were associated with LBW and PTB. We found that HIV status was highly associated with high vaginal microbial diversity. HIV-infected women had significantly higher alpha diversity in their vaginal microbiota, and they were more likely to have CST3. Surprisingly, having a diverse community type was not associated with high levels of vaginal inflammation. However low levels of IL13 and IL-I7 while high levels of TNF-α were associated with HIV status. In conclusion this study found that a highly dysbiotic vaginal environment is characteristics of Zimbabwean pregnant women and that vaginal microbiota is weakly associated with some poor pregnancy outcomes. The high prevalence of L. iners and its association with poor pregnancy outcomes suggests that vaginal microbiota may partly explain the high incidence of adverse pregnancy outcomes in African women. Low level of Th2 cytokines and growth factors may lead to adverse birth outcomes. Longitudinal studies of vaginal microbiota and soluble factors are needed in African women.